The effect of group cognitive behavior hypnotherapy (gcbh) on neuroendocrine and somatic symptoms in patients with anxiety disorders in Nanjing, China - Hanyue, Zhang (2024)
The prevalence of anxiety disorder is increasing and has a significant impact on quality of life. This study aims to determine the effects of group cognitive behavior hypnotherapy on somatic symptoms and neuroendocrine levels in patients with anxiety disorder. This study utilized a randomized control trial design. A total of 84 patients who met the inclusion criteria were randomly selected and assigned to either the intervention group (42 participants) or the control group (42 participants) using computer randomization. After completing psychological measurement scales (Hamilton Anxiety Scale (HAMA), Self-Rating Anxiety Scale (SAS), and Somatic Symptom Self-Rating Scale (SSS)) and blood tests (Cortisol (COR), Serum triiodothyronine (T3), Thyroxine (T4), Thyroid-Stimulating Hormone (TSH) and Adrenocorticotropic Hormone (ACTH)), the intervention group received group cognitive behavior hypnotherapy once a week for six consecutive weeks. The control group only received routine treatment and care. After six weeks, both groups completed the psychological measurement scales (HAMA, SAS, SSS) and blood tests (COR, ACTH, TSH, T3, T4) again. Data was analyzed using a chi-square test and t-test to compare differences between the two groups. The results showed that after group cognitive behavior hypnotherapy, the HAMA score in the experimental group decreased from 24.79±5.479 to 7.52±3.194 (P<0.01), SAS decreased from 59.07±3.047 to 28.14±3.00 , and SSS decreased from 56.12±3.262 to 27.50±1.82 (P<0.001) . The blood test results for COR (581.66±78.241 vs 343.05±50.378 nmol/L), ACTH (14.37±1.481 vs 12.66±0.775 pmol/L), TSH (3.53±0.657 vs 2.83±0.758 mIU/L), T3 (1.22±0.081 vs 0.93±0.041 ng/ml), and T4 (8.32±0.711 vs 6.73±0.638 ng/ml) were all lower than before treatment, with statistical significance (P<0.001). At the same time, the control group showed significant decreases in HAMA (26.88±4.763 VS 19.21±2.464) and SAS(59.07±3.047 VS 28.14±3.000) full scores compared with 6 weeks earlier (P ＜0.001). This study found that group cognitive behavior hypnotherapy can alleviate physical symptoms in patients with anxiety disorders and improve their neuroendocrine levels.